Some aerobic bacterial causes of clinical mastitis in cows &study some causes of treatment failure: Yousif,A.A ;Al-Dulimy,W.A.G; Y; Al-grabawi,M.A. - Al-Dulimy, Yousif A.A. (The Iraqi Journal of Veterinary Medicine, 2008)
The study included 82 clinical mastitic cows (328 quarters) in two dairycattle stations, 15 cows in the first station in Baghdad and 67 cows in thesecond station in Babel, Clinical inspection was conducted on cows and it’sudder, milk samples were collected under sterile condition and subjected forphysical, chemical & bacteriological examination with antibiotic sensitivitytest of the isolated pathogens.The mastitic cows in each station were divided into two groups, the 1st(Treated group) in which cows treated by us and the 2nd (control group) inwhich cows were treated by the staff of station. After treatment all cowswere examined clinically and bacteriologly four times (once 10 days). Swapsfrom milker’s hands and milking machine were also taken.The results revealed that out of 328examined quarters, 212 quarters wereinfected (55 quarter in the 1st station and 157 quarter in the 2nd station). Theacute form of mastitis represent high percent and the occurance of thedisease increased with the advance age. The hind quarters were morefrequently affected than fore ones.Staph.aureus was the only isolate from the 1st station, while 14 type ofbacteria was isolated from the 2nd station .Staph. aureus & Staph.epidermidiswere isolated from milker’s hand,where as Bacillus cereus, Klebsiellapneumoniae . & Pseudomonas aeruginosa & Pasteurella spp. were isolatedfrom teat cups.